UNIT 11.16 Alternative Splicing Signatures in RNA‐seq Data: Percent Spliced in (PSI). (6th October 2015) - Schafer, Sebastian; Miao, Kui; Benson, Craig C.; Heinig, Matthias; Cook, Stuart A.; Hubner, Norbert
Abstract : Thousands of alternative exons are spliced out of messenger RNA to increase protein diversity. High‐throughput sequencing of short cDNA fragments (RNA‐seq) generates a genome‐wide snapshot of these post‐transcriptional processes. RNA‐seq reads yield insights into the regulation of alternative splicing by revealing the usage of known or unknown splice sites as well as the expression level of exons. Constitutive exons are never covered by split alignments, whereas alternative exonic parts are located within highly expressed splicing junctions. The ratio between reads including or excluding exons, also known as percent spliced in index (PSI), indicates how efficiently sequences of interest are spliced into transcripts. This protocol describes a method to calculate the PSI without prior knowledge of splicing patterns. It provides a quantitative, global assessment of exon usage that can be integrated with other tools that identify differential isoform processing. Novel, complex splicing events along a genetic locus can be visualized in an exon‐centric manner and compared across conditions. © 2015 by John Wiley & Sons, Inc.